Art, Design, Media: Memorials of Latin America - La Ferla, Jorge (2021)
On the occasion of the Third DAT Symposium, I propose an analytical journey through a series of exhibitions that took place in Latin America that refer to a memory on the ways of designing, representing and putting into work problems that make critical readings of our continent. They are the various artistic processes that, from the exhibition point of view, think significantly and propose stories about our region and about the same technological visual arts. An analytical panorama that includes experimental cinema, television, video art, multimedia, bio-art as part of a set that questions and critically relates contemporary art with design and media art. These hybrid movements involve contaminations that transcend the borders of the media and that we can consider under the concept of “discursive extremities” as defined by Christine Melo. A tour of the works of Albertina Carri and Andrés Denegri (Argentina), Gilbertto Prado (Brazil), José Alejandro Restrepo (Colombia), Gerardo Suter (Mexico) and Irina Raffo (Uruguay) whose processes I have closely followed offer a significant sample of readings of the continent, which dialogue with the urban context in which they were deployed: Buenos Aires, Mexico, Montevideo, Salta. Exhibitions that propose a reading of personal memories, of particular stories from the recent history of the continent and that refer to the means applied in each sample where the practice of installation prevails, which is deployed under different supports and technological devices.